PENINGKATAN PRESTASI MATA PELAJARAN MATEMATIKA KELAS IVSEMESTER II DENGAN SUB POKOK BAHASAN -SOAL CERITA MELALUI STRATEGI PROBLEM SOLVING DI MI AL-MA'ARIF BULUPAYUNG KECAMATAN PATIMUAN - Sri Hayati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2018)
This research is based on the initial observation in the form of a pre test for mathematics subjects with basic competencies that students must possess that is able to solve everyday problems involving mixed calculations. From the results of the pre-test, the average grade IV students only reached 63, even though the KKM determined was 70. Based on the initial data, the researchers carried out classroom action research with the following problem formulation: